USE OF DIGITAL ECOSYSTEMS IN THE SYSTEM OF PEDAGOGICAL EDUCATION (Education in the 21st Century, 2023)
The article reveals the concept of ecosystem, digital ecosystem, the purpose of its creation and a typical structure. The rating of the most widespread digital ecosystems such as Google, Microsoft, Apple and Amazon on degree of transformation of the information and data is presented. Emphasis is placed on the fact that the main element of any digital ecosystem is Single Sign-On technology, i.e. working with a single account in many digital services. The system of digital services of Microsoft and Google - leaders in the educational system is presented. The advantages of using digital ecosystems in the educational system are analyzed separately, as they perform the functions of creating, accumulating and exchanging information in a single environment, which can serve as a school website, as a window of interaction between the school and the environment. Courses for teachers in the system of postgraduate pedagogical education are presented, aimed at studying digital ecosystems "Digital ecosystems in the educational process of modern school", "Secrets of modern online lesson", which aim is to form the necessary base of theoretical and practical knowledge about digital ecosystems, their structure, advantages, types, educational opportunities and features of use in schools. At the same time, the emphasis is not only on the use of services within one ecosystem, but also on building their own ecosystem of services for the successful organization of the learning process. It is concluded that teachers as leaders in school reform must be able to design lessons using digital ecosystems. In addition, this phenomenon allows organizing internal and external data exchange, management and marketing of educational services. The development and implementation of appropriate thematic courses in the system of postgraduate education will raise the organization of the educational process in each school to a higher level.
Keywords: Keywords: ecosystem, types of ecosystem, digital ecosystems, digital ecosystems in education, advanced training system, teachers.